A Novel Research Method for Determining Sedative Exposure in Critically Ill Patients. Issue 1 (January 2019) - Tracy, Mary Fran; Chlan, Linda; Savik, Kay; Skaar, Debra J.; Weinert, Craig
Abstract : Background: Although potent sedative and opioid drugs are some of the most commonly used medications to manage pain, anxiety, and discomfort in critically ill patients, conducting clinical trials where sedative and opioid medications are outcome variables within a longitudinal research design can be a methodological challenge. Objectives: The purpose of this article is to provide in detail a conceptual discussion of the concept and analysis of sedative exposure : A novel research analysis method for aggregating sedative and opioid medication doses from disparate drug classes commonly administered to critically ill patients and used by our team in several clinical research studies. Methods: Comparing the dose of each sedative and opioid administered to an individual patient (within a defined time interval) to all other patients in a research study receiving the same medications allows for ranking of dosages for each medication by quartiles. Rank values for all sedatives and opioids received can be summed to a single value resulting in a Sedation Intensity Score. In addition, a simple count of how many hours at least one dose of a sedative or opioid medication has been administered can determine sedation frequency. Results: This method can allow for comparison of sedative exposure with medications from disparate drug classes and for analysis of estimates of change in medication use over time. Discussion: This novel research analysis method can overcome the challenges and limitations of determining changes in sedative and opioid medication regimens in cohort and clinical trial study designs.